First-in-human autologous implantation of genetically modified adipocytes expressing LCAT for the treatment of familial LCAT deficiency - Aso, Masayuki; Yamamoto, Tokuo T.; Kuroda, Masayuki; Wada, Jun; Kubota, Yoshitaka; Ishikawa, Ko; Maezawa, Yoshiro; Teramoto, Naoya; Tawada, Ayako; Asada, Sakiyo; Aoyagi, Yasuyuki; Kirinashizawa, Mika; et al. (Heliyon, 2022)
Familial lecithin: cholesterol acyltransferase (LCAT) deficiency (FLD) is a severe inherited disease without effective treatment. Patients with FLD develop severe low HDL, corneal opacity, hemolytic anemia, and renal injury. We developed genetically modified adipocytes (GMAC) secreting LCAT (LCAT-GMAC) for ex vivo gene therapy. GMACs were prepared from the patient’s adipocytes to express LCAT by retroviral gene transduction to secrete functional enzymes. This study aimed to evaluate the safety and efficacy of LCAT-GMAC implantation in an FLD patient. Proliferative preadipocytes were obtained from a patient using a ceiling culture and retrovirally transduced with LCAT. After obtaining enough cells by expansion culture of the transduced cells, the resulting LCAT-GMACs were implanted into a patient with FLD. To evaluate the safety and efficacy, we analyzed the outcome of the autologous implantation for 24 weeks of observation and subsequent 240 weeks of the follow-up periods. This first-in-human autologous implantation of LCAT-GMACs was shown to be safe by evaluating adverse events. The LCAT-GMAC implantation increased serum LCAT activity by approximately 50% of the baseline and sustained over three years. Consistent with increased LCAT activity, intermediate-density lipoprotein (IDL) and free cholesterol levels of the small and very small HDL fractions decreased. We found the hemoglobin/haptoglobin complex in the hemolyzed pre-implantation sera of the patient. After one week of the implantation, the hemoglobin/haptoglobin complex almost disappeared. Immediately after the implantation, the patient's proteinuria decreased temporarily to mild levels and gradually increased to the baseline. At 48 weeks after implantation, the patient's proteinuria deteriorated with the development of mild hypertension. By the treatment with antihypertensives, the patient's blood pressure normalized. With the normalization of blood pressure, the proteinuria rapidly decreased to mild proteinuria levels. LCAT-GMAC implantation in a patient with FLD is shown to be safe and appears to be effective, in part, for treating anemia and proteinuria in FLD. Cholesterol homeostasis; Ex vivo gene therapy; Familial LCAT deficiency; HDL; LCAT; Proteinuria; Renal injury.